Investigating Web impact factors of type 1, type 2 and type 3 medical universities in Iran - Shekofteh, Maryam; Shahbodaghi, Azam; sajjadi, Samad; Jambarsang, Sara (Archives of Advances in Biosciences, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->Investigation of the web impact factor and analysis of the web links belong to webometric studies. A high impact factor, accompanied by more frequent links to a particular website, can indicate greater influence and better accessibility of that particular site. In this regard, bearing in mind the significance of medical universities' web sites for education and research, the current study compared and analyzed their impact factors, their web links and web pages, using AltaVista search engine. The investigation included different ranks of medical universities, commonly referred to as type 1, type 2 and type 3 universities in Iran. The median was used as a measure of central tendency of the scores. The search engines of AltaVista were adopted on 26 February 2010 to collect the data. According to the results, in terms of indexed pages, Shahid Baheshti of type 1, Guilan of type 2, and Shahrekord of type 3 universities had the best records. Regarding web links, medical universities of Iran, Kermanshah and Lorestan, from type 1, type 2 and type 3 universities had the best records and, in terms of impact factor, universities of Ahvaz (type 1), Zahedan (type 2), and Fessa (type 3) manifested the greatest influence. As the results imply, the universities are expected to pay more attention to webometric issues; they are also recommended to allocate more budget to enhance their web pages.